HUBUNGAN ANTARA KELEKATAN ORANG TUA ANAK DAN KOMUNIKASI INTERPERSONAL DENGAN REGULASI EMOSI PADA SISWA SMP MUHAMMADIYAH 5 TULANGAN - Nurdiana, Annisa; Hazim, Hazim (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The purpose of this research is to determine the relationship between parental attachment, interpersonal communication and emotional regulation. This research uses quantitative correlational methods for the relationship between parent-child attachment, interpersonal communication, and emotional regulation in Muhammadiyah 5 Tulangan Middle School students. Sample determination using Isacc and Michael tables with a level of 5% using simple random sampling techniques. The research population consisted of 359 students and the sample selected was 177 children. Research data collection used Armsden Greenberg which was adapted by (Soimatul 2022) the Parent-Child Attachment scale with a reliability value of 0.770, the Interpersonal Communication scale used DeVito's theory which has been adapted by (Cahayantara 2021) with a reliability value of 0.814, and the Emotion Regulation scale used Thamson's theory. has been adapted by (Pamila 2021) with a reliability value of 0.814. The data analysis technique uses multiple correlation analysis and is calculated using the JASP program. The results of this study show R=0.355, p-value .001 that Parent-Child Attachment has a significant relationship with Emotion Regulation. The research results show R=0.295, p-value .001 that Interpersonal Communication has a significant relationship with Emotion Regulation.